Concomitant Duplications of Opioid Peptide and Receptor Genes before the Origin of Jawed Vertebrates - Sundström, Görel (Public Library of Science, 2010)
BACKGROUND: The opioid system is involved in reward and pain mechanisms and consists in mammals of four receptors and several peptides. The peptides are derived from four prepropeptide genes, PENK, PDYN, PNOC and POMC, encoding enkephalins, dynorphins, orphanin/nociceptin and beta-endorphin, respectively. Previously we have described how two rounds of genome doubling (2R) before the origin of jawed vertebrates formed the receptor family. METHODOLOGY/PRINCIPAL FINDINGS: Opioid peptide gene family members were investigated using a combination of sequence-based phylogeny and chromosomal locations of the peptide genes in various vertebrates. Several adjacent gene families were investigated similarly. The results show that the ancestral peptide gene gave rise to two additional copies in the genome doublings. The fourth member was generated by a local gene duplication, as the genes encoding POMC and PNOC are located on the same chromosome in the chicken genome and all three teleost genomes that we have studied. A translocation has disrupted this synteny in mammals. The PDYN gene seems to have been lost in chicken, but not in zebra finch. Duplicates of some peptide genes have arisen in the teleost fishes. Within the prepropeptide precursors, peptides have been lost or gained in different lineages. CONCLUSIONS/SIGNIFICANCE: The ancestral peptide and receptor genes were located on the same chromosome and were thus duplicated concomitantly. However, subsequently genetic linkage has been lost. In conclusion, the system of opioid peptides and receptors was largely formed by the genome doublings that took place early in vertebrate evolution.